KOLABORASI ANTARA PEMERINTAH, SWASTA, DAN MASYARAKAT SIPIL DALAM PELAKSANAAN KEBIJAKAN PUBLIK: MODEL SINERGI UNTUK PENGEMBANGAN DAERAH - Muhammad Tegar Satriatama; Achmad Nurmandi; Herman Lawelai (Fakultas Politik Pemerintahan IPDN, 2025)
Abstract This study aims to analyze and develop a synergy model of collaboration between the government, the private sector, and civil society in the implementation of public policies at the regional level. This multi-actor collaboration is seen as an important approach to improve the effectiveness of public policies, especially in the context of sustainable regional development. This study explores how the interaction between the three actors can be enhanced through efficient collaborative mechanisms. In addition, the study identifies key factors that affect the success of collaboration, such as coordination challenges, differences in priorities, and operational mechanisms that have not been integrated. The results of this study are expected to make an important contribution to the development of better collaborative governance at the local level and offer practical recommendations for decision-makers to create innovative and sustainable solutions in the implementation of public policies. Keywords: Collaboration, Public Policy, Civil Society, Government, Private, Synergy, Regional Development, Governance.